DESIGN AND MODELLING OF LINEAR GENERATORS FOR WAVE ENERGY CONVERSION FOR UN-MANED PLATFORM - Tan, You Zhang (IRC, 2019)
The un-maned platform requires 1kW power supply for basic operation such as lighting system, protection system and protection system. Normally, the power for un-maned platform is supplied by solar panel. However, the solar panel had many drawbacks in term of big installed area, large storage area for battery, unpredictable weather and unreliable power supply. In this research, wave energy conversion technology is introduced to generate electricity for un-maned platform. The main objective of this project is to design and model linear generator that produces 1 kW power for power supply on un-maned platform. The linear generators topology are proposed for better efficiency and simulated and optimized by using finite element software. In conducting this project, the literature review on wave energy conversion linear generator such as type of generator, power take off method, stator and rotor configuration had been conducted. There are twelve designs with the different type of magnet arrays have been proposed in order to select the best design for the linear generator. By using Ansys Maxwell software, the results in term of magnetic flux line distribution, air gap flux density, flux linkage and induced voltage had been obtained through simulation. The magnetic flux line distribution is equal for all magnet array designs. The air gap flux density and flux linkage had contribute to the induced voltage for all magnet array designs which enough to supply enough power for un-maned platform. Based on the result, top six performance magnet array designs are redefined and optimized through pitch ratio and split ratio method. Then, the designs have been compared and the highest efficiency design will be proposed for prototyping and analyzing.